Fewer ligament injuries but no preventive effect on muscle injuries and severe injuries: an 11-year follow-up of the UEFA Champions League injury study - Ekstrand, J.; Hägglund, M.; Kristenson, K.; Magnusson, H.; Walden, M. (British Journal of Sports Medicine, 2013)
Background: Limited information is available on the variation in injury rates over multiple seasons of professional football. Aim: To analyse time-trends in injury characteristics of male professional football players over 11 consecutive seasons. Methods: A total of 1743 players comprising 27 teams from 10 countries were followed prospectively between 2001 and 2012. Team medical staff recorded individual player exposure and time loss injuries. Results: A total of 8029 time loss injuries were recorded. The match unavailability due to injury was 14% and constant over the study period. On average, a player sustained two injuries per season, resulting in approximately 50 injuries per team and season. The ligament injury rate decreased during the study period (R2=0.608, b=-0.040, 95% CI -0.065 to -0.016, p=0.005), whereas the rate of muscle injury (R2=0.228, b=-0.013, 95% CI -0.032 to 0.005, p=0.138) and severe injury (R2=0.141, b=0.015, 95% CI -0.013 to 0.043, p=0.255) did not change over the study period. In addition, no changes in injury rates over the 11-year period were found for either training (R2=0.000, b=0.000, 95% CI -0.035 to 0.034, p=0.988) or match play (R2=0.282, b=-0.015, 95% CI -0.032 to 0.003, p=0.093). Conclusions: The injury rate has decreased for ligament injuries over the last 11 years, but overall training, match injury rates and the rates of muscle injury and severe injury remain high.